The Effect of Electoral System Reforms on Political Representation and Accountability in the Indonesian Legislative Elections - Amanda, Nurawaliah (Generasi Sains Indonesia, 2025)
This study investigates the impact of electoral system reforms on political representation and accountability in Indonesia’s legislative elections from 1999 to 2024. Following democratization after the fall of the New Order regime, Indonesia implemented major institutional changes, including the shift from a closed-list to an open-list proportional representation system, the introduction of electoral thresholds, and the enforcement of a 30 percent gender quota. Using a mixed-methods approach that combines longitudinal electoral data with qualitative evidence from interviews and document analysis, the study examines three dimensions: proportionality and party system dynamics, gender representation, and legislative accountability. The findings indicate that electoral reforms have improved vote–seat proportionality and reduced excessive party fragmentation, contributing to greater electoral stability. Women’s representation in parliament has increased over time, although persistent structural and cultural barriers continue to constrain substantive gender equality. In addition, indicators of accountability such as legislative attendance, constituency engagement, and public trust show moderate improvement, suggesting that open-list competition encourages more responsive behavior among legislators. However, accountability remains largely personalized rather than institutionalized, relying on individual visibility instead of collective performance. Overall, Indonesia’s electoral reforms have supported gradual democratic consolidation, while remaining constrained by clientelism and weak institutional accountability.